Condições de eluição para purificação de anticorpos policlonais de coelho por cromatografia de afinidade - Dias, Natália Aragão (2021)
Polyclonal antibodies can be used for diagnostic medicine applications in infectious and immunological diseases. Rabbits have a strong immune response against foreign organisms due to their mechanism regarding the production of different antibodies. Antibodies from rabbit serum have some advantages over other mammalian antibodies: simpler structure of IgG, higher ligand affinity and faster reproductive cycle. In addition, they produce more different types of antibodies. Protein A (Staphylococcus aureus) has been widely used to purify antibodies. This work aims to study the best elution conditions to purify polyclonal antibodies from rabbit serum using affinity chromatography technology in a Protein A column. Through literature research, it was possible to establish initial conditions to operate the chromatographic runs. They consisted in 4 steps: Loading, Wash, Elution and Regeneration. The sample concentration in the initial tests was 2.5 mg mL-1. The buffer chosen in Loading, Wash and Regeneration steps was Sodium Phosphate buffer 25mM pH 7.0. Chromatographic runs were performed using Sodium Citrate buffer 100mM pH 3.3 and Glycine-HCl buffer 100mM pH 2.8. Both had satisfactory results, but Glycine-HCl showed a higher specificity to the protein. SDS-PAGE Electrophoresis was performed to identify the proteins in the collected samples. The chromatograms presented a satisfactory profile: they formed well defined peaks in the elution, which were analyzed through the collected samples. Electrophoresis was performed to identify proteins in the collected samples. At the end of the washing step the presence of practically isolated rabbit serum albumin was observed. In the elution stage, the presence of rabbit IgG purer than the standard was observed. The subsequent tests carried out using different sample concentrations: 1.0 mg mL-1 and 5 mg mL-1. The results showed that the serum concentration did not have influence in the percentage of retained protein from the initial sample. Chromatographic runs with different buffer molarities were also performed (50 mM, 100 mM, 200 mM, 500 mM e 1000 mM). The best results were collected from the run which elution step consisted of Glycine-HCl buffer 100mM pH 2.8 with 2.5 mg mL-1of sample loading. Dot Blot Technique detected the presence of rabbit IgG purified from all chromatographic runs. Thus, it is concluded that the buffer Glicina-HCl pH 2.8 and Sodium Citrate pH 3.3 were effective in the process of purification of immunoglobulin G from the diluted rabbit serum.